Regulation of Mitochondrial Dynamics by Aerobic Exercise in Cardiovascular Diseases - Gu, Changping; Yan, Jie; Zhao, Liang; Wu, Guanghan; Wang, Yue-lan (Frontiers in Cardiovascular Medicine, 2022)
Mitochondrial dynamics, including continuous biogenesis, fusion, fission, and autophagy, are crucial to maintain mitochondrial integrity, distribution, size, and function, and play an important role in cardiovascular homeostasis. Cardiovascular health improves with aerobic exercise, a well-recognized non-pharmaceutical intervention for both healthy and ill individuals that reduces overall cardiovascular disease (CVD) mortality. Increasing evidence shows that aerobic exercise can effectively regulate the coordinated circulation of mitochondrial dynamics, thus inhibiting CVD development. This review aims to illustrate the benefits of aerobic exercise in prevention and treatment of cardiovascular disease by modulating mitochondrial function.